The Use Of Antibiotics And Supportive Therapy On Length Of Hospital Stay In Children With Severe Pneumonia : Literature Review - yanti, risma; Ferdi, Ferdi; Saputri, Sena; Anggraini, Ribi; Kurniawati, Dian; Lasorea, Mahardika; Mutmainnah, Adhe Wasti; Lestari, Sri Mayang; Alamsyah, Muh. Yusuf; Purnamasari, Anisa (Nursing Genius Journal, 2025)
Background: Severe pneumonia is one of the leading causes of death among children under the age of five, particularly in developing countries. WHO data from 2021 reported approximately 70,000 child deaths annually worldwide. The morbidity and mortality associated with severe pneumonia remain high due to factors such as comorbidities, delayed diagnosis, lack of medical services, and malnutrition. Purpose: To identify the recovery time, influencing factors in recovery, and a systematic approach to the treatment of severe pneumonia in children, including the use of antibiotics. Methods: A systematic literature search was conducted in the PubMed and Google Scholar databases using Boolean terms and filters for the years 2023–2025. Results: The search yielded 10 articles that met the specified criteria and keywords. Children who received early antibiotic treatment showed faster and more stable recovery progress. Nutrition and vitamin D played a significant role in accelerating the healing process. Conclusion: Early detection, antibiotic administration, supportive care, and a holistic treatment approach significantly impact the reduction of recovery time and the risk of severe pneumonia in children.